Chromatin structural rearrangement during dedifferentiation of protoplasts of Cucumis sativus L - Ondrej, Vladan; Kitner, Miloslav; Dolezalová, Ivana; Nádvorník, Petr; Navrátilová, Bozena; Lebeda, Ales (Molecules and cells, 2009)
This paper reports on the structural rearrangement of satellite DNA type I repeats and heterochromatin during the dedifferentiation and cell cycling of mesophyll protoplasts of cucumber (Cucumis sativus). These repeats were localized in the telomeric heterochromatin of cucumber chromosomes and in the chromocenters of interphase nuclei. The dramatic reduction of heterochromatin involves decondensation of subtelomeric repeats in freshly isolated protoplasts; however, there are not a great many remarkable changes in the expression profile. In spite of that, reformation of the chromocenters, occurring 48 h after protoplast isolation, is accompanied by recondensation of satellite DNA type I; however, only partial reassembly of these repeats was revealed. In this study, FISH and a flow cytometry assay show a correlation between the partial chromocenter and the repeats reassembly, and with the reentry of cultivated protoplasts into the cell cycle and first cell division. After that, divided cells displayed a higher variability in the expression profile than did leaves' mesophyll cells and protoplasts.
Keywords: Genome, Plant; genom rostlinný; centromera; hybridizace in situ fluorescenční; Centromere; separace buněk; buněčná diferenciace; stanovení celkové genové exprese; Protoplasts; chromozomy rostlin; Flow Cytometry; Chromosomes, Plant; chromatin; Gene Expression Profiling; DNA rostlinná; Chromatin; DNA, Plant; průtoková cytometrie; protoplasty; Cell Separation; Cucumis sativus; In Situ Hybridization, Fluorescence; Cell Differentiation